Pegilated interferon α2а in treatment of chronic hepatitis C - P. O. Bogomolov; S. V. Koblov; A. O. Buyeverov; M. V. Matsiyevich; O. S. Kuzmina; N. A. Barsukova; N. V. Dubinina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze experience of pegIFN-α 2а (Pegasys®) application at combined antiviral therapy of chronic hepatitis C (CHC) within the framework of the Moscow regional regional program on viral hepatites treatment.Material and methods. Overall 369 patients underwent treatment since 2008 to 2011, of them 292 patients – with CHC. Male patients prevailed in the studied group – 202 (54,74%), female patients – 167 (45,26%), mean age was 41,1 years. Prior to therapy onset needle liver biopsy was carried out in 88,3% of patients, subsequently liver cirrhosis was diagnosed in 77 patients. In 227 of patients the 1-st HCV genotype was revealed, 2nd genotype – in 24, 3rd genotype – in 41cases.Results. Sustained virologic response (SVR) after the termination of antiviral therapy was achieved in 70,1% of patients. Statistically significant differences by gender, body mass index, virus genotype were revealed between groups which have achieved and not achieved SVRs. Anemia, leukopenia, thrombocytopenia, thyropathy and depression were marked as the most frequent undesirable treatment effects.Conclusions. Follow-up of CHC patients, treated by pegIFN-α2а and ribavirin in the Moscow regional hepatological center, testifies its high efficacy and safety profile.